2007
DOI: 10.1016/j.engstruct.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight bamboo double layer grid system

Abstract: The paper presents the structural and environmentally sustainable aspects of bamboo as a valid construction material. A special PVC joint designed for bamboo double layer grids (DLG) is presented and implemented in a 2.3 × 2.3 × 0.9 m DLG module. Experimental results obtained from evaluating two bamboo species, proof loading of the proposed PVC joint and loading of the DLG module are presented and compared to numerical predictions. The results indicate that the proposed DLG system can be used in practice for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 3 publications
1
27
0
1
Order By: Relevance
“…Biomaterials like wood, bamboo, and rattan are promising construction materials because they are sustainable and environmentally friendly (Lakkad and Patel 1981;Amada et al 1997). Compared with wood, bamboo grows faster, can be harvested in 3 to 5 years, and has a similar or higher strength-to-weight ratio than wood (Nogata and Takahashi 1995;Albermani et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials like wood, bamboo, and rattan are promising construction materials because they are sustainable and environmentally friendly (Lakkad and Patel 1981;Amada et al 1997). Compared with wood, bamboo grows faster, can be harvested in 3 to 5 years, and has a similar or higher strength-to-weight ratio than wood (Nogata and Takahashi 1995;Albermani et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Wood and bamboo are attractive engineering materials due to their renewability, easy accessibility, low energy consumption and pollution, and their high strength-to-mass ratio (Liese 1987;Simpson and TenWolde 1999;Jiang and Peng 2007;Fakoor and Rafiee 2013). As an abundant natural resource in Asia, bamboo has been used as a non-structural and structural material in many areas (Chung and Yu 2002;Albermani et al 2007;Xiao et al 2009;Deng et al 2014a): as bamboo-based, compositecovered bamboo particleboard (Zhang et al 1997), bamboo fiberboard (Matsumoto et al 2001), bamboo strandboard (Sumardi et al 2006), and bamboo-bundle laminated veneer lumber (Deng et al 2014b,c;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al (2015) focused on the role of bamboo nodes relative to culm stiffness and strength, and the experimental results indicated that the node could be explained as an attempt to reinforce a biologically essential feature, which would otherwise be a point of weakness when loaded in tension and bending. The mechanical properties and connecting joints of bamboo culm are suitable for a lightweight bamboo double layer grid system for construction applications (Albermani et al 2007). An investigation of the effect of uniaxial and biaxial compression loadings on the circumferential-radial mechanical properties has shown that the diametric strength of bamboo evaluated by biaxial load was 2.4 to 2.5 times the uniaxial compression (Jiang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, strength of polyvinyl chloride (PVC) and bamboo adhesive joints was experimentally investigated by Albermani et al (2007). In their work, the bamboo ends were encased inside the cylindrical connector made of PVC using a megapoxy grouting material.…”
Section: Joining Techniquesmentioning
confidence: 99%